Origin of Relaxor Behavior in Barium‐Titanate‐Based Lead‐Free Perovskites. (10th November 2021) - Veerapandiyan, Vignaswaran; Popov, Maxim N.; Mayer, Florian; Spitaler, Jürgen; Svirskas, Sarunas; Kalendra, Vidmantas; Lins, Jonas; Canu, Giovanna; Buscaglia, Maria Teresa; Pasciak, Marek; Banys, Juras; Groszewicz, Pedro B.; et al.
Abstract: It is well known that disordered relaxor ferroelectrics exhibit local polar correlations. The origin of localized fields that disrupt long‐range polar order for different substitution types, however, is unclear. Currently, it is known that substituents of the same valence as Ti 4+ at the B‐site of barium titanate lattice produce random disruption of TiOTi chains that induces relaxor behavior. On the other hand, investigating lattice disruption and relaxor behavior resulting from substituents of different valence at the B‐site is more complex due to the simultaneous occurrence of charge imbalances and displacements of the substituent cation. The existence of an effective charge mediated mechanism for relaxor behavior appearing at low (< 10%) substituent contents in heterovalent modified barium titanate ceramics is presented in this work. These results will add credits to the current understanding of relaxor behavior in chemically modified ferroelectric materials and also acknowledge the critical role of defects (such as cation vacancies) in lattice disruption, paving the way for chemistry‐based materials design in the field of dielectric and energy storage applications. Abstract : In BaTiO3 solid solutions, relaxor behavior is caused by lattice disorder disrupting long‐range ferroelectricity. In this work, it is shown that introducing donor substituents at the B‐site of BaTiO3 leads to the formation of clusters of charged defects (involving Ti vacancies) as a charge‐compensation mechanism, which leads to an earlier onset of relaxor behavior compared to homovalent‐substituted systems.